Impacto ambiental del metano producido pro el ganado vacuno, criado bajo dos sistemas de explotación, en la ganadería "monte carmelo" - Trujillo - Abanto Rojas, Elí Manuel (2011)
The environmental impact of methane produced by cattle beef, reared under two farming systems, has led this research, whose objective was to determine which of the farming system generates major negative environmental impact by the emission of methane. In order to do that, 60 days each samples of fodder, concentrated, as well as manure forage and concentrate food were taken and then were analyzed and quantified, in order to determine the amount of methane emitted. The results indicated that the emission expressed by fecal excretes produced by animals live weight was 67,78% more in extensive production systems. As well as the methane production expressed by the energy consumption by animal/day was 17,80% smaller in the extensive production system. However, methane emissions estimated by livestock surface or utilized was 79,67% greater than in intensive production systems. It was concluded that the extensive production system feed from forage generates less negative environmental impact compared to food from concentrate in the intensive system that generates the greatest negative environmental impact.